2004
DOI: 10.1364/ol.29.000343
|View full text |Cite
|
Sign up to set email alerts
|

Long-period-grating-assisted optical add–drop filter based on mismatched twin-core photosensitive-cladding fiber

Abstract: A noninterferometric optical fiber add-drop channel filter based on a mismatched twin-core photosensitive-cladding fiber and long-period fiber grating is demonstrated. With assistance from the fiber grating, co-directional spectrally selective cross coupling between the two cores can be realized with an efficiency of 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In another study, it has been numerically demonstrated that a grating-assisted semilinear coupler can support very slow BG solitons 61 . Such structures can be produced with current technology by writing a uniform or nonuniform grating in one of the two cores 5658 . BG solitons in dual core systems can be a potential candidate for various novel optical devices (e.g., all-optical soliton diode reported in ref.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it has been numerically demonstrated that a grating-assisted semilinear coupler can support very slow BG solitons 61 . Such structures can be produced with current technology by writing a uniform or nonuniform grating in one of the two cores 5658 . BG solitons in dual core systems can be a potential candidate for various novel optical devices (e.g., all-optical soliton diode reported in ref.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions may be satisfied for rich scattering radio channels beyond direct visibility range. Lately, there have been attempts to use MIMO concept in lightwave transmission over multimode (MM) fibers [3][4][5]. They are based on the analogy between mutipath radio transmission and (inter)modal dispersion in MM fibers.…”
Section: Resultsmentioning
confidence: 99%
“…They are proposed for application in the fields of optical communications [1,2], components [3,4], and optical sensors [5,6] because of their compact and potential applications such as fiber laser [7], optical tweezer [8], and nonlinear devices [9]. A major inconvenience associated with the using of TCFs is the difficulty in both exciting and detecting signals in the two cores.…”
mentioning
confidence: 99%
“…(24,26,50) it has been shown that semilinear couplers, where only the nonlinear core is equipped with uniform or nonuniform BG, can indeed support quiescent and moving BG solitons. Such gratings can readily be produced with the current technology by writing a uniform or nonuniform grating on one or both cores in the coupling region (51)(52)(53). Coupled BGs are strong candidates for optical add-drop elements in WDM networks (54,55).…”
Section: Introductionmentioning
confidence: 99%